Construction de Variétés de Groupes Exceptionnels Non $k$-Rationnelles - Gille, Philippe (MATHEMATICA SCANDINAVICA, 2015)
Our goal is to construct non $k$-rational varieties of exceptional groups. The relevant invariant is the defect of weak approximation.